Endocannabinoid signaling in psychiatric disorders: a review of positron emission tomography studies - Sloan Matthew E.; Grant Caroline W.; Gowin Joshua L.; Ramchandani Vijay A.; Foll Bernard Le (Acta Pharmacologica Sinica, 2019)
Endocannabinoid signaling is implicated in an array of psychopathologies ranging from anxiety to psychosis and addiction. In recent years, radiotracers targeting the endocannabinoid system have been used in positron emission tomography (PET) studies to determine whether individuals with psychiatric disorders display altered endocannabinoid signaling. We comprehensively reviewed PET studies examining differences in endocannabinoid signaling between individuals with psychiatric illness and healthy controls. Published studies evaluated individuals with five psychiatric disorders: cannabis use disorder, alcohol use disorder, schizophrenia, post-traumatic stress disorder, and eating disorders. Most studies employed radiotracers targeting cannabinoid receptor 1 (CB1). Cannabis users consistently demonstrated decreased CB1 binding compared to controls, with normalization following short periods of abstinence. Findings in those with alcohol use disorder and schizophrenia were less consistent, with some studies demonstrating increased CB1 binding and others demonstrating decreased CB1 binding. Evidence of aberrant CB1 binding was also found in individuals with anorexia nervosa and post-traumatic stress disorder, but limited data have been published to date. Thus, existing evidence suggests that alterations in endocannabinoid signaling are present in a range of psychiatric disorders. Although recent efforts have largely focused on evaluating CB1 binding, the synthesis of new radiotracers targeting enzymes involved in endocannabinoid degradation, such as fatty acid amide hydrolase, will allow for other facets of endocannabinoid signaling to be evaluated in future studies.